2018
DOI: 10.22158/uspa.v1n1p89
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Some Socio-Demographic Aspects under One Health Approach in Eastern Tanzania: Connections and Realities

Abstract: Health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Lower and Middle-Income Countries (LMICs) adopted community participation in health service delivery in primary health care through decentralization by devolution policies, which created Health Facility Governing Committees (HFGCs) [5][6][7] . The created HFGCs are devolved with speci c functions and powers to perform in the course of governing primary health care facilities 8,9 . LMICs are implementing different types of decentralization such as scal decentralization to primary health facilities and HFGCs to improve the health service delivery at the PHC 10 .…”
mentioning
confidence: 99%
“…Lower and Middle-Income Countries (LMICs) adopted community participation in health service delivery in primary health care through decentralization by devolution policies, which created Health Facility Governing Committees (HFGCs) [5][6][7] . The created HFGCs are devolved with speci c functions and powers to perform in the course of governing primary health care facilities 8,9 . LMICs are implementing different types of decentralization such as scal decentralization to primary health facilities and HFGCs to improve the health service delivery at the PHC 10 .…”
mentioning
confidence: 99%
“…This condition is directly associated with worse health outcomes, with poorer health choices, poorer understanding of health conditions, the inability to clearly understand medical information and preventive health measures. Poor health literacy is also associated with an increase in hospital stays/admissions and consequently with an increase in health-related expenses (Berkman, Davis, & McCormack, 2010;Muhanga, & Malungo, 2018;Cho, Lee, Arozullah, & Crittenden, 2008, Agency for Health Care Research and Quality 2011).) Other scientific evidence has shown that individuals with inappropriate health literacy levels have more problems when they have to deal with basic health activities, to follow prescriptions, to calculate the quantity of medicines they have to take, to communicate with health providers, to interpret the results of their medical testing and to understand the risks and benefits of different medical procedures (National Network of Libraries of Medicine, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, better levels of literacy positively influence health, impacting health care costs and utilization, disease promotion and prevention. On the other hand, inadequate health literacy has a negative impact on one's ability to access and use health care, interact with professionals and take care of oneself (Berkman, Davis, & McCormack, 2010;Muhanga, & Malungo, 2018). It also shows that when the level of health literacy is inappropriate, it can negatively affect the capacity of a person to access and use health care resources, to interact with the health professionals and to take care of him/herself (Berkman, Davis, & McCormack, 2010;Muhanga, & Malungo, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations